The sapphire widow [large type] - Jefferies, Dinah, 1948- (Thorndike Press large print basic series., 2018)
From the author of The Tea Planter's Wife comes a sweeping story of love and betrayal set in Ceylon in 1935. Louisa Reeve, the daughter of a British gem trader, and her husband Elliot, a charming, thrill-seeking businessman, seem to have it all. Except the one thing they long for: a child. After Elliott's sudden death, Louisa is left alone to solve the mystery he left behind.